Implementasi Program Kesejahteraan Karyawan di Perusahaan Global: Analisis Sistematis Faktor Keberhasilan dan Tantangan Lintas Budaya - Fatimah, Fatimah; Anshori, M. Isa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research explores the implementation of employee welfare programs in multinational companies through a systematic literature review. This study analyzes in depth the latest empirical research (2019-2024) that highlights success factors and challenges in a cross-cultural context. By applying the PRISMA protocol, this research identified key patterns in program implementation, including the importance of ROI evaluation, the influence of local cultural values, and the effect of ESG activities on employee psychological well-being. The research results show that the success of the program depends on the effective integration of economic, social and cultural aspects, as well as contextual adjustments in its implementation. These findings form the basis for designing a more efficient framework for managing employee well-being at a global level.